More than Fit: Brand Extension Authenticity - Spiggle, Susan; Nguyen, Hang T.; Caravella, Mary (Journal of Marketing Research, 2012)
This article introduces a new determinant of brand extension success, brand extension authenticity (BEA), as a complement to fit. The authors develop the BEA construct and a scale to measure it and then demonstrate that BEA captures consumer perceptions of brand extension legitimacy and cultural contiguity along four interrelated but distinct dimensions: maintaining brand standards and style, honoring brand heritage, preserving brand essence, and avoiding brand exploitation. They demonstrate the power of BEA in predicting consumer reactions to brand extensions, particularly among consumers with strong self–brand connections. Not only is BEA distinct from two conceptualizations of fit in brand extension literature—fit as similarity and fit as relevance—but it also moderates the effects of both fit dimensions on brand extension responses. By capturing a cultural and consumer relational perspective that shapes reactions to brand extensions, BEA provides an important, complementary construct for predicting brand extension success and enhancing brand value. Brand managers attentive to BEA may be able to stretch brands further than assessments of fit alone would suggest, but they risk failure in otherwise well-fitting extensions perceived as inauthentic.